PCs all-in-one for dummies - Chambers, Mark L. (John Wiley & Sons, 2013)
Whether you use your PC for work or play, there's a lot to learn and a lot of territory to discover, so take along a good guide. Serving up nine meaty minibooks, this All-in-One guide covers essential PC topics from soup through nuts, including the latest on PC hardware, Windows 8, the Internet, all the tools in Office 2013, digital media, troubleshooting and maintenance, upgrading your PC, home networking, and PC gaming. You'll get to know your PC inside and out and find yourself turning to this terrific resource again and again.